Bacteroides fragilis concealed in an infant with Escherichia coli meningitis. (9th October 2013) - Ganeshalingham, Anusha; Buckley, David; Shaw, Ian; Freeman, Joshua T; Wilson, Francessa; Best, Emma
Abstract Anaerobic meningitis in infants is rare, therefore a high index of clinical suspicion is essential as routine methods for processing cerebrospinal fluid (CSF) do not detect anaerobes and specific antimicrobial therapy is required. We present an infant with Escherichia coli meningitis where treatment‐resistance developed in association with culture negative purulent CSF. These features should have alerted us to the presence of anaerobes, prompting a search for the causes of polymicrobial meningitis in infants.